2023
DOI: 10.1186/s12967-023-04036-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG cell-free supernatant as a novel anti-cancer adjuvant

Abstract: Background Gut microbiota modulation has been demonstrated to be effective in protecting patients against detrimental effects of anti-cancer therapies, as well as to improve the efficacy of certain anti-cancer treatments. Among the most characterized probiotics, Lactobacillus rhamnosus GG (LGG) is currently utilized in clinics to alleviate diarrhea, mucositis or intestinal damage which might be associated with several triggers, including Clostridium difficile infections, inflammatory gut diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The study by Salemi et al revealed that the cell-free supernatant of L. rhamnosus GG (LGG-SN) specifically and concentration-dependently reduces the survival of cancer cells. For cancer cell lines, the relative IC 50 values vary from 91.8% LGG-SN (v/v) for the less sensitive Caco-2 cells to 73.8% LGG-SN (v/v) for HT-29 and 74.8% LGG-SN (v/v) for A375, respectively 57 . According to the MTT analysis of Vachkova et al Lacticaseibacillus paracasei strains can inhibit the growth of HT-29 cells in a dose-dependent manner 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Salemi et al revealed that the cell-free supernatant of L. rhamnosus GG (LGG-SN) specifically and concentration-dependently reduces the survival of cancer cells. For cancer cell lines, the relative IC 50 values vary from 91.8% LGG-SN (v/v) for the less sensitive Caco-2 cells to 73.8% LGG-SN (v/v) for HT-29 and 74.8% LGG-SN (v/v) for A375, respectively 57 . According to the MTT analysis of Vachkova et al Lacticaseibacillus paracasei strains can inhibit the growth of HT-29 cells in a dose-dependent manner 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, several studies confirmed the potential role of postbiotics in preventing and treating cancer, particularly CRC. By this means, Salami et al demonstrated that Lactobacillus rhamnosus GG could selectively reduce the viability of cancer cells, such as HT-29 cells, in a dose-dependent way, with a mitotic arrest the cell cycle in the G2/M phase 28 . Some studies, such as Shyu et al, focus on the anti-proliferative and apoptosis effects of Lactobacillus species in various cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the pH of the postbiotics was brought to a physiological range (pH 7.2–7.4) by employing 5 M sodium hydroxide, and the solution was filtered through a 0.22 μm polyethersulfone membrane syringe filter (Millipore, USA). This process was carried out prior to conducting the anti-proliferation and anti-migration assays 28 .…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic activity in melanoma cells was comparable to the one recorded for the anticancer conventional drug 5-FU when LP was used in concentrations of 10 10 and 10 9 CFU/mL; similar concentrations of L. rhamnosus selectively reduced viability in A375 melanoma cells in a concentration-dependent manner [ 27 ]. 5-FU is usually associated with mucositis, diarrhea, myelosuppression, cardio- and neurotoxicity that make systemic treatment difficult for cancer patients; the use of LP may therefore replace a highly toxic anticancer therapy with a more acceptable one in terms of quality of life for the treated patients.…”
Section: Discussionmentioning
confidence: 80%